(3QSGdI aj YOO MQha GdbQBfs ((3CMeO QaYJ s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje YOO GdCMQa GdJi ai GdbQBf Ydi GdJaUjd bGd Gdabjg QVi Gddg Yfg CdaGJ KeGfjI hCQHYhf CdakG s
(3BNQgG (B:s
(3GdjGA NeSI hYTQhf CdakG hJSYeGFI hJSYI YTQ jGA bGd GdabjI QVi Gddg Yfg hai gPG ENJdGa cKjQ dCf LeGYI ef GdbQGA bGdhG HgPG GdeYfi hCgd GdJaSjQ hGddg CYde JeJ s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdbQGAGJ hGdJLhjOs